Haemoglobin variability in the early post‐transplant period: Association with graft survival and mortality. Issue 2 (20th January 2013) - Rozen‐Zvi, Benaya; Ben‐Avraham, Binjamin; Schneider, Shira; Gafter‐Gvili, Anat; Levy‐Drummer, Rachel S; Zingerman, Boris; Mor, Eitan; Gafter, Uzi; Rahamimov, Ruth
<x xml:space="preserve">Abstract</x> This study demonstrates that high haemoglobin variability in the first 6 months post‐transplant is independently associated with inferior graft survival in patients after kidney transplantation. While no inference on the effect of haemoglobin variability on outcomes can be made, the association is very interesting and warrants further consideration.